2021
DOI: 10.1039/d1gc03472c
|View full text |Cite
|
Sign up to set email alerts
|

Chrome-free tanning agent based on epoxy-modified dialdehyde starch towards sustainable leather making

Abstract: As a biomass tanning agent, epoxy-modified dialdehyde starch can significantly improve the comprehensive properties of finished leather, and is expected to be a novel sustainable chrome-free tanning agent replace traditional tanning agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…First, the starch was introduced into the aldehyde group by a reaction with sodium periodate, which oxidized it to form dialdehyde starch (Figure S1). As illustrated in Figure A, a new characteristic peak was observed in the Fourier transform infrared (FTIR) spectrum of DAS located at 1733 cm –1 , corresponding to the characteristic peak of carbonyl groups (CO), which confirmed that some hydroxyl groups in starch had been oxidized by NaIO 4 . This was also evidenced by a new peak at 1721 cm –1 in the CO stretching vibration of DAS in the Raman spectrum (Figure B).…”
Section: Resultsmentioning
confidence: 76%
“…First, the starch was introduced into the aldehyde group by a reaction with sodium periodate, which oxidized it to form dialdehyde starch (Figure S1). As illustrated in Figure A, a new characteristic peak was observed in the Fourier transform infrared (FTIR) spectrum of DAS located at 1733 cm –1 , corresponding to the characteristic peak of carbonyl groups (CO), which confirmed that some hydroxyl groups in starch had been oxidized by NaIO 4 . This was also evidenced by a new peak at 1721 cm –1 in the CO stretching vibration of DAS in the Raman spectrum (Figure B).…”
Section: Resultsmentioning
confidence: 76%
“…However, leather production generally necessitates a tanning process . During this process, hazardous heavy metal ions (e.g., Cr 3+ ) are generally involved, which can cause potential environmental issues and increase cancer risk in humans during long contact with these leather products. Therefore, seeking a porous, permeable, durable, eco-friendly, and biofriendly staring material for constructing functional and smart insoles is of great significance but is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the polyhydroxy structures of oligosaccharides, aldehyde group-rich oligosaccharide derivatives can be produced through oxidization. Once these species are synthesized, a robust crosslinking network is weaved via forming multisite Schiff base structures between the aldehyde group in the oligosaccharides and the amino group in the collagen fibers [4,5]. For example, biomass-derived aldehyde (BDA) tanning agents were prepared through periodate oxidation of sodium carboxymethyl cellulose (CMC) and sugarcane bagasse, in which the C2-C3 bond of the glucose unit was selectively cleaved to form 2,3-dialdehyde CMC [6,7].…”
Section: Biomass Derived Oligosaccharides For Potential Leather Tanningmentioning
confidence: 99%